Effects of knowledge sharing behavior on innovative work behavior among nursing Students: Mediating role of Self- leadership. (2020) - Asurakkody, Thanuja Ariyasinghe; Kim, Sang Hee
Abstract: Background: Individual innovation is fundamental to organizational performance in an ever-changing world. Employers today need individuals who can share knowledge and self-direct because they achieve organizational outcomes. Purpose: This research aims to explore the relationship between knowledge sharing and innovative work by assessing the mediating role of self-leadership. Methods: This cross-sectional descriptive study applied data from 148 nursing students from a public nursing school in Sri Lanka. Results: Generally, our findings show a significant positive relationship between knowledge sharing behavior and innovative work behavior and that self-leadership fully mediate the relationship. Conclusions: Overall, this study will contribute to educational organizations in healthcare by providing insights into the roles of knowledge sharing and self-leadership in stimulating nursing students' development and helping them become future innovators.